A Healthy Lifestyle and Purchase Intention on Food Claims - Ramadhan, Nadya Salsabila; Cempaka, Laras; David, Wahyudi (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2024)
Nowadays, consumers are selective in choosing their healthy food. A healthy lifestyle as well as food claims are prominent factors that motivate consumers to purchase healthy food. This study aims to determine and analyze the relationship between a healthy lifestyle on purchase intention on food products with claims. Healthy Promoting Lifestyle-II (HPLP-II) measured for a healthy lifestyle. The data analysis includes descriptive tests, classical assumption tests (normality test, linearity test, and multicollinearity test), and multiple linear regression analysis tests. Based on the test results, 99% of respondents are aware of food products with claims, 93% of respondents often see food products with nutrition claims, 80% of respondents often see dairy products and their preparation as food products with claims, and 96% of respondents choose food products with claim rather than without claims. Scores of indicators of a healthy lifestyle with the maximum score is 5.00 (physical activity 3.85, healthy diet 3.73, quality of sleep 3.59, and non-smoking behavior 4.57 in this study exceeded the minimum scores (≥2.50). Healthy lifestyle, age, income, and education simultaneously affect purchase intention in food products with claims.